2018
DOI: 10.1615/critrevbiomedeng.2018026093
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Protein Structure Prediction Using Lattice Model

Abstract: The prediction of the tertiary structure of a protein from its primary sequence is a long-standing problem for life science researchers. Solutions to this problem have a direct impact on other research areas such as design and discovery of new drugs, understanding the sequenced genomic data, solving the puzzle of protein structure, and understanding the folding mechanism. Solving protein structure prediction (PSP) is considered a cornerstone for life science research to reveal the mechanism of cellular process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the case of the anticipated tertiary structure by the Swiss Model, the assessment experiment executed by the Ramachandran Map (PROCHECK) indicated that 93% of the total residues (227) were found in the core, 7.0% of residues were found in the additional allowed regions, and there was no residue found in the abundantly authorized parts and the disallowed areas [22,23]. The number of non-glycine and non-proline residues was 244, which was 100%, and the end residues were four; the glycine and proline residues were 20 and 8, respectively, among the 276 total residues (Figure 1).…”
Section: Tertiary-structure Modeling and Validationmentioning
confidence: 99%
“…In the case of the anticipated tertiary structure by the Swiss Model, the assessment experiment executed by the Ramachandran Map (PROCHECK) indicated that 93% of the total residues (227) were found in the core, 7.0% of residues were found in the additional allowed regions, and there was no residue found in the abundantly authorized parts and the disallowed areas [22,23]. The number of non-glycine and non-proline residues was 244, which was 100%, and the end residues were four; the glycine and proline residues were 20 and 8, respectively, among the 276 total residues (Figure 1).…”
Section: Tertiary-structure Modeling and Validationmentioning
confidence: 99%
“…One well-known application is the Ising model of ferromagnetism in statistical mechanics [15]. In biophysics, protein folding is commonly described by a class of lattice models of compact polymers in which the constituent amino acids are constrained to occupy a regular array of positions in space [16,17]. Lattice-based models have also been used to model cellular proliferation and migration, as well as pattern formation [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophobic-polar (HP) model is one of the most widely accepted models to study protein folding and the PSP problem at a coarse level. 4 Although, the HP model has reduced the complexity of the PSP problem, the possible search space is vast. Dubey et al provide solutions in the second paper entitled, "A Comparative Study on Single and Multiple Point Crossovers in Genetic Algorithms for Coarse Protein Modeling."…”
mentioning
confidence: 99%